2006
DOI: 10.1111/j.1582-4934.2006.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in decorin and biglycan in Duchenne Muscular Dystrophy: role of fibroblasts as cell source of these proteoglycans in the disease

Abstract: Fibrosis is a common pathological feature observed in muscles of patients with Duchenne muscular dystrophy (DMD). Biglycan and decorin are small chondroitin/dermatan sulfate proteoglycans in the muscle extracellular matrix (ECM) that belong to the family of structurally related proteoglycans called small leucine-rich repeat proteins. Decorin is considered an anti-fibrotic agent, preventing the process by blocking TGF-β activity. There is no information about their expression in DMD patients. We found an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 52 publications
(41 reference statements)
1
56
0
Order By: Relevance
“…We have revealed that both the digested core protein and the glycosylated form are of higher intensity in DMD fibroblast media than in control media. Fadic et al (2006) have also reported increased decorin (and also biglycan synthesis) in muscle-derived fibroblasts from a DMD patient compared with controls. Kuroda and Shinkai (1997) have detected higher levels of decorin transcripts in systemic sclerosis fibroblasts, and Westergren- Thorsson et al (2004) have reported increased levels of decorin secreted by primary fibroblasts derived from a fibrotic lung.…”
Section: Discussionmentioning
confidence: 87%
“…We have revealed that both the digested core protein and the glycosylated form are of higher intensity in DMD fibroblast media than in control media. Fadic et al (2006) have also reported increased decorin (and also biglycan synthesis) in muscle-derived fibroblasts from a DMD patient compared with controls. Kuroda and Shinkai (1997) have detected higher levels of decorin transcripts in systemic sclerosis fibroblasts, and Westergren- Thorsson et al (2004) have reported increased levels of decorin secreted by primary fibroblasts derived from a fibrotic lung.…”
Section: Discussionmentioning
confidence: 87%
“…They bind several ECM and plasma membrane proteins during skeletal muscle differentiation, regulating myogenesis (Riquelme et al, 2001;Casar et al, 2004;Droguett et al, 2006;Mercado et al, 2006;Rafii et al, 2006;Cabello-Verrugio and Brandan, 2007). In recent years much interest has been given to the role of decorin in satellite cell myogenesis and muscle regeneration, for its ability to modulate myoblast responsiveness to members of the TGF-β family which in turns affect fibrosis, muscle differentiation and regeneration (Caceres et al, 2000;Riquelme et al, 2001;Sato et al, 2003;Fadic, 2005;McCroskery et al, 2005;Fadic et al, 2006;Cabello-Verrugio and Brandan, 2007).…”
Section: Proteoglycans In Skeletal Musclementioning
confidence: 99%
“…After 6 h, cells were infected with an adenovirus that contained human decorin whole sequence (38) using 500 plaque-forming units/cell in 4 ml of DMEM supplemented with 2% of heat-inactivated fetal bovine serum (38). After 90 min of incubation, standard growing medium was added, and the incubation was continued for 24 h. Cells were incubated with growing factors or radiolabeled with H 2 [ 35 S]SO 4 (23). Decorin and Deletion Mutants of Decorin-The wild type decorin and the mutants that lack different LRRs were generated by overlapping PCR starting from human decorin (NM_133593) cloned in pcDNA 3.1 (kindly donated by Elke Schönherr, Institute of Physiological Chemistry and Pathobiochemistry, Münster, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Duchenne muscular dystrophy is a disease caused by the absence of the protein dystrophin, which produces muscle weakness that leads to cycles of degeneration and regeneration of the muscle fibers, resulting in a decrease of muscle mass and an increase of connective tissue (21)(22)(23)(24). In this way, fibrotic scarring ensues, and the regeneration of muscle is precluded by this fibrotic scar.…”
mentioning
confidence: 99%
See 1 more Smart Citation